Removal of Large Wharton’s Duct Salivary Stones Using a CO2 Laser: A Report of Two Cases - Matsumoto, Kousuke; Tanakura, Makiko; Mitani, Izumi; Kimoto, Akira; Akashi, Masaya (Journal of Lasers in Medical Sciences, 2021)
Introduction: Salivary stones inside the Wharton’s duct adjacent to the mylohyoid muscle are often removed by a little incision of the mouth floor under local anesthesia. However, in the case of relatively large salivary stones, a large incision is required, which is commonly accompanied by hemorrhage and the need for surgical hemostasis, resulting in prolonged surgery. Furthermore, troublesome sequelae such as ranula and lingual nerve paralysis can occur after surgical procedures. Methods: Two patients who had relatively large salivary stones (>1 cm diameter) in the Wharton’s duct was underwent incision of the mouth floor soft tissues with a CO2 laser. Results: In both patients, the stone was removed in a few minutes without causing abnormal bleeding, nerve injury, or sublingual gland disorders and was completely healed. Conclusion: We report the usefulness and safety of the CO2 laser in two patients with relatively large salivary stones, who underwent successful surgical removal. DOI: 10.34172/jlms.2021.19